Shrinking core? Exploring the differential agenda setting power of traditional and personalized news media. Issue 6 (12th September 2016) - Moeller, Judith; Trilling, Damian; Helberger, Natali; Irion, Kristina; De Vreese, Claes
Abstract : Purpose: This paper aims to shed light on the impact of personalized news media on the shared issue agenda that provides democracies with a set of topics that structure the public debate. The advent of personalized news media that use smart algorithms to tailor the news offer to the user challenges the established way of setting the agenda of such a common core of issues. Design/methodology/approach: This paper tests the effects of personalized news use on perceived importance of these issues in the common core. In particular, the authors study whether personalized news use leads to a concentration at the top of the issue agenda or to a more diverse issue agenda with a long tail of topics. Findings: Based on a cross-sectional survey of a representative population sample ( n = 1, 556), we find that personalized news use does not lead to a small common core in which few topics are discussed extensively, yet there is a relationship between personalized news use and a preference for less discussed topics. This is a result of a specific user profile of personalized news users: younger, more educated news users are more interested in topics at the fringes of the common core and also make more use of personalized news offers. Research limitations/implications: The results are discussed in the light of media diversity and recent advances in public sphere research. Originality/value: This paper contributes to the ongoing debate about algorithmic news dissemination. While, currently, much attention is reserved for the role of platforms as information gatekeepers in relationship to the news media, maybe their ability to enable or hinder the audience in discovering and distributing news content is part of what really characterizes their influence on the market place of ideas.